#TITLE_ALTERNATIVE# - PRAMA EKAPUTRA (NIM : 20211309) ; Pembimbing Prof. Dr.Eng. Khairurrijal , Dr. Eng. Muhammad , MUHAMAD
Nanofibrous membrane based on Polyacrylonitrile (PAN) for water purification application has been successfully synthesized in this study. The membrane was synthesized by using electrospinning technique. This technique has advantages in terms of processing, effectiveness, production scale (both small scale and industrial scale), and controlling of nanofiber. The superiorities of nanofibrous membrane produced by electrospinning are its high porosity, interconnected porous system, allowing good permeability and filtering performance. The concentration of PAN solution used in electrospinning method was varied at 6, 8, and 10 percent by weight.The membrane yielded was characterized by Scanning Electron Microscopy (SEM) in order to assess the morphology and diameter. Evaluation of membrane included flux test and filtration efficiency analysis towards suspension containing solid particles (as antacid) and bacterial suspension of P. Aeruginosa and S. Epidermidis, with respective concentration of 3.02 × 107 sel/ml and 2.89 × 107 sel/ml. All evaluation performed in this study was compared with membrane filter for High Performance Liquid Chromatography (HPLC) solvent as a control membrane. In order to evaluate the degree of purity of the filtrate,the concentration of solid particle and bacteria were determined prior to and after filtration using spectrophotometry (for antacid) and hemocytometry (for bacteria). PAN membrane with the most optimum characteristics was then developed further as nanofibrous membrane with atibacterial activity by electrospinning with addition of chitosan to the structure. The mixture of PAN and chitosan was varied with mass ratio at 10:1, 10:1, dan 5:1. SEM analysis showed fine and uniform strands of PAN fiber with diameter ranging from 270 to 310 nm for 6 weight percent, 290 – 370 nm for 8 weight percent, and 440 – 540 nm for 10 weight percent. Addition of chitosan into PAN membrane resulted in the formation of beads scattered within the strands of fiber. Analysis of filtration efficiency demonstrated reduction of bacterial and particle concentration following fitration using all the membranes. Significant reduction was observed in filtration using pure PAN membrane at 8 weight percent, with filtration efficiency of 94.56 - 99.48 %. Absorbance of filtrate of antacid suspensions at 322 nm was negligible, indicating that almost all the particles were removed. However, filtrate yielded from filtration using PAN membrane 10 weight percent contained 29.35 ppm of antacid particles. Incorporation of chitosan into PAN nanofibrous membrane affected flux profiles. Furthermore, PAN/Chitosan membrane demonstrated antibacterial activity. The lowest rate of bacterial growth was observed in membrane with the highest Chitosan/PAN ratio. In summary, characterization and membrane evaluation v indicated that nanofibrous membrane based on PAN with 8 weight percent was highly potential for application as filtration medium for water effectively and efficiently.